Angiodysplasia of left colon extending to anal verge landed patient into APR: a rare finding - Jain, Amit; Jain, Divya (International Surgery Journal, 2018)
Angiodysplasias is a kind of vascular malformation preferably involves the veins. Angiodysplasia of colon is the second most common cause of lower gastrointestinal bleeding after diverticulosis. It usually involves caecum and ascending colon. Patient may either present with complaints of fresh bleeding per rectum or with melena. It usually occurs in elderly because of age related degeneration of small blood vessel walls. The case presented here involves a male patient of 25-year age with complains of intermittent bleeding per rectum and generalized weakness from one month. After examination it was found to have vascular ectasia involving mid transverse colon, left colon and the rectum coming down to anal verge which culminated into abdominoperineal resection. Biopsy of resected segment came to be angiodysplasia with external surface of specimen showing dilation of multiple vascular channels in entire length up to anal verge. This case report shows that though angiodysplasia is more common in old age but while exploring a young patient with lower gastrointestinal tract bleeding, and congestive changes are found in left colon possibility of angiodysplasia should also be kept in mind.